Empowering Future Professionals: A Project-Based Learning and Positive Psychology Model for Academic Writing in an EFL Context - Sakkir, Geminastiti; Nur, Sahril; Sahril Nurfadhilah, Auliyanti (Har Press Indonesia, 2025)
Academic writing is a cornerstone of higher education, yet for English as a Foreign Language (EFL) students, it presents significant challenges related to linguistic competence, genre mastery, and writing anxiety. This study investigates the impact of a novel pedagogical model integrating Project-Based Learning (PjBL) and Positive Psychology (PP) on multiple dimensions of student engagement. The study was conducted within a compulsory